Obsessive-Compulsive Personality Disorder Co-occurring in Individuals with Obsessive-Compulsive Disorder: A Systematic Review and Meta-analysis. Issue 2 (March 2021) - Pozza, Andrea; Starcevic, Vladan; Ferretti, Fabio; Pedani, Carolina; Crispino, Roberta; Governi, Guido; Luchi, Simonetta; Gallorini, Antonella; Lochner, Christine; Coluccia, Anna
Abstract : Supplemental digital content is available in the text. Abstract : Learning objectives: After participating in this activity, learners should be better able to: Assess the rates of co-occurring obsessive-compulsive personality disorder (OCPD) in patients with obsessive-compulsive disorder (OCD) Identify characteristics related to OCD with co-occurring OCPD Abstract: The current literature discloses discrepant findings regarding the rates of co-occurring obsessive-compulsive personality disorder (OCPD) in patients with obsessive-compulsive disorder (OCD). In addition, it is not clear which characteristics are related specifically to OCD with co-occurring OCPD. We conducted the first systematic review and meta-analysis of the studies of the prevalence of OCPD in patients with OCD. We also investigated potential moderators of the prevalence, including OCD severity, age of onset of OCD, sex, current age, methodological quality, and publication date of the studies. Electronic databases and gray literature were searched by two independent reviewers. A PRISMA systematic review with a random-effect meta-analysis was conducted. Thirty-four studies were included. A significant mean effect size of 0.25 without publication bias indicated that OCPD was present in 25% of patients with OCD, suggesting that the two conditions are distinct clinical entities. This prevalence was higher than the rates found in the literature for any other personality disorders among OCD patients. OCPD that occurs in the context of OCD was more likely to be present in males and to be characterized by a later age of onset of OCD, older age at assessment, and less severe OCD symptoms. Clinicians should consider these findings when assessing and planning treatment of OCD with co-occurring OCPD.